CO2 strong chemisorption as an estimate of coal char gasification reactivity (1999)
ABSTRACT: In this article, coal char gasification reactivity was correlated with the strong chemisorption of CO2 at 3008C. Chars of as-received, demineralized, K and Fe loaded coals were prepared at 8008C, under high purity nitrogen. The CO2 chemisorption method described in this article allows differentiation between two types of chemisorption that takes place at low temperatures: strong CO2 chemisorption (irreversible) which is related to the presence of the active inorganic components of the char, and weak CO2 chemisorption (reversible) which is because of the organic matter of the char. The char doped with K showed the highest CO2 strong chemisorption and at the same time the highest reactivity in the CO2 gasification, while the char loaded with Fe had the highest amount of weak chemisorption. It was found that total chemisorption (weak 1 strong) at 3008C depends on the CO2 pressure of the analysis. The reactivity of the CO2 gasification of the char was normalized using the value of the amount of CO2 strongly chemisorbed at 3008C. q 1999 Elsevier Science Ltd. All rights reserved.